Tomato Seed Yield Depending on Pre-Sowing Treatment - Shapko, Maryna; Shevchenko, Nadiia; Kovalenko, Galyna; Kuts, Oleksandr (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):305